Occurrence of pesticide residues in indoor dust of farmworker households across Europe and Argentina - Navarro, Irene; De la Torre, Adrián; Sanz, Paloma; Baldi, Isabelle; Harkes, Paula; Huerta-Lwanga, Esperanza; Nørgaard, Trine; Glavan, Matjaž; Pasković, Igor; Polić Pasković, Marija; Abrantes, Nelson; Campos, Isabel; et al. (Elsevier, 2023)
Pesticides are widely used as plant protection products (PPPs) in farming systems to preserve crops against pests, weeds, and fungal diseases. Indoor dust can act as a chemical repository revealing occurrence of pesticides in the indoor environment at the time of sampling and the (recent) past. This in turn provides information on the exposure of humans to pesticides in their homes. In the present study, part of the Horizon 2020 funded SPRINT project, the presence of 198 pesticide residues was assessed in 128 indoor dust samples from both conventional and organic farmworker households across Europe, and in Argentina. Mixtures of pesticide residues were found in all dust samples (25–121, min-max; 75, median). Concentrations varied in a wide range (<0.01 ng/g-206 μg/g), with glyphosate and its degradation product AMPA, permethrin, cypermethrin and piperonyl butoxide found in highest levels. Regarding the type of pesticides, insecticides showed significantly higher levels than herbicides and fungicides. Indoor dust samples related to organic farms showed a significantly lower number of residues, total and individual concentrations than those related to conventional farms. Some pesticides found in indoor dust were no longer approved ones (29 %), with acute/chronic hazards to human health (32 %) and with environmental toxicity (21 %).